2010
DOI: 10.5194/bg-7-187-2010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of peat quality on microbial greenhouse gas formation in an acidic fen

Abstract: Abstract.Peatlands play an important role in the global carbon cycle and represent both an important stock of soil carbon and a substantial natural source of relevant greenhouse gases like CO 2 and CH 4 . While it is known that the quality of organic matter affects microbial degradation and mineralization processes in peatlands, the manner in which the quality of peat organic matter affects the formation of CO 2 and CH 4 remains unclear. In this study we developed a fast and simple peat quality index in order … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 71 publications
6
32
1
Order By: Relevance
“…The observation that microbial activity on soil carbon mass basis was higher for the soils with higher quality carbon is consistent with a number of previous reports (Groffman et al, 1991;Schipper et al, 1994;Hill and Cardaci, 2004). Several peatland studies also have demonstrated that both CO 2 and CH 4 production are related to the lability of soil organic carbon compounds Bridgham and Richardson, 1992;Crozier et al, 1995), suggesting that carbon quality has a strong influence on rates of greenhouse gas production (Bridgham and Richardson, 1992;Wagner et al, 2005;Reiche et al, 2010).…”
Section: Role Of Electron Donors: Carbon Quantity and Qualitysupporting
confidence: 78%
“…The observation that microbial activity on soil carbon mass basis was higher for the soils with higher quality carbon is consistent with a number of previous reports (Groffman et al, 1991;Schipper et al, 1994;Hill and Cardaci, 2004). Several peatland studies also have demonstrated that both CO 2 and CH 4 production are related to the lability of soil organic carbon compounds Bridgham and Richardson, 1992;Crozier et al, 1995), suggesting that carbon quality has a strong influence on rates of greenhouse gas production (Bridgham and Richardson, 1992;Wagner et al, 2005;Reiche et al, 2010).…”
Section: Role Of Electron Donors: Carbon Quantity and Qualitysupporting
confidence: 78%
“…Nevertheless, the relationships between the measured SOM parameters used to assess the biochemical decomposability, CO 2 emissions and Q 10 values were rather weak and thus do not support our second hypothesis. This stands in contrast to other studies which concluded that chemical composition is a major factor of SOM decomposability in organic soils (Scanlon and Moore, 2000;Koch et al, 2007;Reiche et al, 2010;Hardie et al, 2011;Leifeld et al, 2012). However, these studies focused mainly on single profiles of undisturbed or extensively used organic soils.…”
Section: Co 2 Emissions and Temperature Sensitivity Of Decompositioncontrasting
confidence: 46%
“…The protection of organic matter (OM) against decomposition by mechanisms such as occlusion in aggregates and binding to mineral surfaces, which are important for the stabilization of OM in mineral soils (Six et al, 2002), are of minor importance in organic soils due to the lack or low abundance of minerals (Han et al, 2016). Therefore, the intrinsic decomposability of organic matter is considered another major factor influencing the rate of peat decomposition and a major cause of substantial variation in CO 2 emissions at different sites (Chimner and Cooper, 2003;Byrne and Farrell, 2005;Höper, 2007;Wickland and Neff, 2008;Reiche et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The highest rates of anaerobic CH 4 production occurred in samples close to the soil surface with fresh peat accumulation and a high water table (Glatzel et al, 2004). The largest anaerobic CO 2 and CH 4 production were found in peat samples close to the soil surface (Reiche et al, 2010). Our findings show that it is not the quality of the bulk peat substrate itself but the presence of fresh organic matter that determines anaerobic GHG production.…”
Section: Onset Of Methanogenesis and Magnitude Of Ch 4 Emissionsmentioning
confidence: 53%